Contribution of Emotional Maturity and Social Support to Self-Adjustment of Santri in Musthafawiyah Purbabaru Islamic Boarding School - Helsa Nasution; Daharnis Daharnis; Syahniar Syahniar (Journal of Educational and Learning Studies, 2019)
This research aims to describe the contribution of emotional maturity and social support to self-adjustment of santri in Pesantren. This research used descriptive quantitative method. The population of this research was 2,695 santri of the 1st grade in Musthafawiyah Purbabaru Islamic Boarding School. The sample were 349 santri and selected by proportional random sampling. The research findings showed: (1) on average, emotional maturity is in the high level category, (2) social support is also at a high level, (3) the self-adjustment of santri is good category, (4) contribution of emotional maturity towards self-adjustment is 44.3%, (5) contributions of social support toward the self-adjustment is 25.9%, and (6) contributions of emotional maturity and social support to the self-adjustment is 48.3%.